Sub-national stratification of malaria risk in mainland Tanzania: a simplified assembly of survey and routine data - Thawer, Sumaiyya G.; Chacky, Frank; Runge, Manuela; Reaves, Erik; Mandike, Renata; Lazaro, Samwel; Mkude, Sigsbert; Rumisha, Susan F.; Kumalija, Claud; Lengeler, Christian; Mohamed, Ally; Pothin, Emilie; et al. (Malaria journal, 2020)
Background Recent malaria control efforts in mainland Tanzania have led to progressive changes in the prevalence of malaria infection in children, from 18.1% (2008) to 7.3% (2017). As the landscape of malaria transmission changes, a sub-national stratification becomes crucial for optimized cost-effective implementation of interventions. This paper describes the processes, data and outputs of the approach used to produce a simplified, pragmatic malaria risk stratification of 184 councils in mainland Tanzania. Methods Assemblies of annual parasite incidence and fever test positivity rate for the period 2016–2017 as well as confirmed malaria incidence and malaria positivity in pregnant women for the period 2015–2017 were obtained from routine district health information software. In addition, parasite prevalence in school children ( Pf PR 5to16 ) were obtained from the two latest biennial council representative school malaria parasitaemia surveys, 2014–2015 and 2017. The Pf PR 5to16 served as a guide to set appropriate cut-offs for the other indicators. For each indicator, the maximum value from the past 3 years was used to allocate councils to one of four risk groups: very low (< 1% Pf PR 5to16 ), low (1− < 5% Pf PR 5to16 ), moderate (5− < 30% Pf PR 5to16 ) and high (≥ 30% Pf PR 5to16 ). Scores were assigned to each risk group per indicator per council and the total score was used to determine the overall risk strata of all councils. Results Out of 184 councils, 28 were in the very low stratum (12% of the population), 34 in the low stratum (28% of population), 49 in the moderate stratum (23% of population) and 73 in the high stratum (37% of population). Geographically, most of the councils in the low and very low strata were situated in the central corridor running from the north-east to south-west parts of the country, whilst the areas in the moderate to high strata were situated in the north-west and south-east regions. Conclusion A stratification approach based on multiple routine and survey malaria information was developed. This pragmatic approach can be rapidly reproduced without the use of sophisticated statistical methods, hence, lies within the scope of national malaria programmes across Africa.